Elevational speciation in action? Restricted gene flow associated with adaptive divergence across an altitudinal gradient. (1st October 2015) - Funk, W. C.; Murphy, M. A.; Hoke, K. L.; Muths, E.; Amburgey, S. M.; Lemmon, E. M.; Lemmon, A. R.
Abstract: Evolutionary theory predicts that divergent selection pressures across elevational gradients could cause adaptive divergence and reproductive isolation in the process of ecological speciation. Although there is substantial evidence for adaptive divergence across elevation, there is less evidence that this restricts gene flow. Previous work in the boreal chorus frog ( Pseudacris maculata ) has demonstrated adaptive divergence in morphological, life history and physiological traits across an elevational gradient from approximately 1500–3000 m in the Colorado Front Range, USA. We tested whether this adaptive divergence is associated with restricted gene flow across elevation – as would be expected if incipient speciation were occurring – and, if so, whether behavioural isolation contributes to reproductive isolation. Our analysis of 12 microsatellite loci in 797 frogs from 53 populations revealed restricted gene flow across elevation, even after controlling for geographic distance and topography. Calls also varied significantly across elevation in dominant frequency, pulse number and pulse duration, which was partly, but not entirely, due to variation in body size and temperature across elevation. However, call variation did not result in strong behavioural isolation: in phonotaxis experiments, low‐elevation females tended to prefer an average low‐elevation call over a high‐elevation call, and vice versa for high‐elevation females, but this trend was not statistically significant. In summary, our results show that adaptive divergence across elevation restricts gene flow in P. maculata, but the mechanisms for this potential incipient speciation remain open.